One-week longitudinal daily description of moral distress, coping, and general health in healthcare workers during the first wave of the COVID-19 outbreak in Italy: A quantitative diary study: COVID-19, moral distress, coping, and general health in healthcare workers - Manara, Duilio F.; Villa, Giulia; Korelic, Lisa; Arrigoni, Cristina; Dellafiore, Federica; Milani, Valentina; Ghizzardi, Greta; Magon, Arianna; Giannetta, Noemi; Caruso, Rosario (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the work .The fluctuation from day to day within a working week of moral distress, coping, and general health of frontline healthcare workers (HCWs) in facing the challenges of the COVID-19 pandemic has been poorly studied. This study described the weekly fluctuation from day to day of moral distress, coping, and general health in frontline HCWs who worked during the first epidemic wave (May-June 2020) of the COVID-19 pandemic in Italy.Methods. This study has an intensive longitudinal design, and a convenience sampling procedure was employed to enroll physicians, nurses, allied health professions, and healthcare assistants. Data collection was performed using diary encompassed four sections: a socio-demographic form (required only at the baseline data collection) and three scales to assess moral distress, coping, and general health.Results. Results confirmed poor perceived health and mild moral distress in frontline HCWs, especially in HCWs with offspring, during the initial phases of the COVID-19 pandemic and the stability of their daily perception over a working week regarding moral distress, general health, and avoidant coping strategy, while approach coping strategy reported a slight fluctuation over time.Conclusions. Accordingly, on the one hand, these results confirm that outcomes regarding mental health and moral distress are pretty stable and provide insights, on the other hand, regarding the possible organizational interventions to support approach coping strategy as it seems more susceptible to variation over time.